Promoter Methylation Status and Protein Expression of BRCA2 in Patients with Epithelial Ovarian Cancer - Ahmad Shabanizadeh; Hajar Dahim; Reza Salahshoor; Zahra Taghipour; Mohammad Mohsen Taghavi; Hamidreza Gafarineveh; Bahram Eslami; Zahra Babazadeh; Farangis Fatehi (Middle East Journal of Cancer, 2013)
Background: Ovarian cancer is the leading cause of death among gynecological cancers. Changes in the methylation of BRCA1 and BRCA2 may be an effective mechanism for breast and ovarian cancer. This study evaluates the protein expression and methylation status of BRCA2 in Iranian patients.Methods: We assessed 60 Mullerian-type ovarian cancers by methylation-specific PCR assays and immunohistochemistry. Results: According to methylation status analysis, there were 7 of 60 (11.66%) methylated cases that had low protein expression.Conclusion: We concluded that changes in the methylation status of BRCA2 cannot be used as an appropriate biomarker to ascertain the development of ovarian cancer.